RESPON PETANI APEL TERHADAP INDUSTRIALISASI PERTANIAN (Kasus di Desa Poncokusumo, Kecamatan Poncokusumo, Kabupaten Malang) - NUR BALADINA; RATYA ANINDITA; RESNA PUTRI NK (Sepa, 2021)
The objective of this research are: (1) Analyzing the response of apple farmers to the agricultural industrialization in Poncokusumo Village, and (2) Identify social economic factors that influence the decisions of farmers to the agricultural industrialization in Poncokusumo Village. The location choosing by purposively in Poncokusumo Village because it is currently implementing agropolitan concept with agricultural industrialization program and apple is one of the leading agricultural commodities are widely cultivated in this area.